Bortezomib for chronic relapsing thrombotic thrombocytopenic purpura: a case report. Issue 8 (24th March 2014) - Yates, Sean; Matevosyan, Karen; Rutherford, Cynthia; Shen, Yu‐Min; Sarode, Ravi
<x xml:space="preserve">Abstract</x> Background Acquired thrombotic thrombocytopenic purpura (TTP) is an autoimmune disorder characterized by a severe deficiency of ADAMTS13 activity. Although therapeutic plasma exchange (PLEX) is the standard of care, 30% to 50% patients develop exacerbation or relapse, requiring immunomodulatory agents. Of these agents, glucocorticoids, rituximab, and cyclosporine A are the most frequently used. Case Report We report a case of chronic relapsing TTP in a patient who had eight relapses over a 14‐year period. After her seventh relapse, the patient demonstrated only partial response to glucocorticoids, two courses of rituximab, and cyclophosphamide. The eighth relapse occurred 58 days after her last PLEX and subsequent to this she received a course of bortezomib (Velcade, Millennium Pharmaceuticals, Inc.). After treatment with bortezomib the patient demonstrated a complete response with a progressive increase in ADAMTS13 activity from less than 5% to 22% accompanied by undetectable inhibitor, and she has remained PLEX free for more than 169 days. Conclusion Bortezomib may serve as an adjunct treatment in patients with acquired TTP who exhibit an incomplete response or are refractory to conventional management.